STUDI ANALISIS TAFSIR, TAKWIL DAN HERMENEUTIKA DALAM MEMAHAMI AL-QUR’AN - Suparman, Yogi; Soga, Zainudin (LPPM STAI Al-Azhary Cianjur, 2024)
The purpose of this research is to analyze tafsir, takwil and hermeneutics in understanding the Quran. This research uses a qualitative approach and literature study method. Based on the results of the research, tafsir and takwil are familiar terms among Muslims, while hermeneutics may still be unfamiliar to some people. Tafsir is the science used to understand the holy book revealed to the Prophet Muhammad SAW, explaining its meaning, law, and wisdom. Takwil is identical to tafsir, which is the transfer of the meaning of a word from a stronger meaning to a weaker meaning because of supporting evidence. Meanwhile, hermeneutics functions as a method of interpreting a text, which includes the text, author, and reader. The difference in purpose between tafsir/takwil and hermeneutics, where tafsir/takwil aims to understand the meanings in the Qur'an, while hermeneutics aims to study and examine the authenticity of a sacred text. Hermeneutics is not very relevant to the Qur'ān, because the Qur'ān is a divine revelation and an unquestionable holy book.